Endovascular Management of Two Uncommon Cases of Acute Upper Limb Ischemia in Young - Utagi, Basavaraj; Kumar, Ruhi; Bhagavan, K.R. (Journal of Health and Allied Sciences NU, 2022)
Acute upper limb ischemia accounts for less than 5% of all cases of limb ischemia. The etiology in young individuals are usually traumatic. Other non-traumatic causes are rarely seen and here we present two such cases in young, presenting with acute upper limb ischemia. The choice between a surgical or a minimally invasive endovascular approach remains unclear. Endovascular approach to management, although based on expertise, offers good post procedural outcome, comparable to post-surgical outcomes. Here we present two cases of thrombotic occlusion of the upper extremity following trauma and arterial thoracic outlet syndrome respectively managed successfully with endovascular approach.
Keywords: upper limb ischemia; peripheral angioplasty; cervical rib; post-traumatic brachial artery thrombosis; in-graft stenosis